Effect of altitude on football performance: Analysis of the 2010 FIFA World Cup data - Nassis, G. P. (The Journal of Strength and Conditioning Research, 2013)
Laboratory studies show that altitude ascent impairs endurance performance. Limited data exist on football, and information from official matches is very scarce even for other team sports. The aim of this study was to examine the effect of altitude on football performance during the 2010 World Cup in South Africa. It was hypothesized that (a) total distance covered, an index of endurance, would be reduced above the altitude of 580 m, and (b) technical skills would be affected because altitude alters ball flight characteristics. Physical performance, goals scored, and goalkeepers' errors that resulted in goals conceded were recorded from the official game statistics of Fédération Internationale de Football Association during the South Africa 2010 World Cup. Matches were played at sea level (altitude: 0 m), 660, 1200-1400, and 1401-1753 m. After testing for data normality, mean differences were checked with a one-way analysis of variance. Results show a 3.1% lower total distance that was covered by the teams during the matches played at 1200-1400 and 1401-1753 m (p < 0.05) compared with sea level. Indices of technical skills, including number of goals scored per game and errors made by the goalkeepers that resulted in goals conceded, did not differ with altitude. It is concluded that playing football above 1200 m had negative effects on endurance but not on technical skills during World Cup 2010 matches. It seems that teams should follow several days of acclimatization before playing at altitude as low as 1200 m, to ameliorate the negative effects of altitude on physical performance.